PENGAJARAN NILAI-NILAI AKHLAK ISLAM DALAM BUKU TA’LIM AL-‘ARABIYYAH BI TARIQAH HADITHAH KARYA M. FETHULAH GÜLEN - Syukur Prihantoro (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2018)
M. Fethullah Gülen, a Turkish Muslim scholar in Islamic education emphasizes better aspects of character and moral building for students in an educational process. Education is not only limited on intelligence, but a clean heart must be the key. The idea of moral teaching is done by integrating religious knowledge with the lesson materials. This research is trying to dissect Gulen's book of Arabic learning with descriptive analysis method. From this study, it was found that the materials he included were the admonition, interpretation and analysis of Qur'anic verses, some hadith chosen, and the stories of the best examples from Sahabah. However, without putting aside the aspect of proficiency in Arabic, Gülen also composed the qawa‘id al-lughah (nahwu and sarf), conversations (al-hiwar), presentation of Arabic vocabulary through image visualization and others. This shows that the book, Ta'lim al-Arabiyyah, of his work is a breaking style of learning Arabic in the Ottoman period that has classical model.